Nilai Filosofis Longgo dan Langga dalam Pembentukan Karakter Masyarakat Gorontalo - Haslan Y. Usman; Sutrisno Mohamad; Irvan Tasnur (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the philosophical values embedded in the traditional martial arts of Longgo and Langga and their role in shaping the character of the Gorontalo community within a contemporary socio-cultural context. Employing a qualitative descriptive design, data were collected through participant observation, in-depth interviews, and documentation involving customary leaders, trainers, and practitioners. The findings reveal that Longgo and Langga function not merely as systems of physical defense but as culturally embedded practices that integrate symbolic meanings, social norms, and spiritual principles. These practices facilitate the internalization of core values, including courage, self-control, discipline, solidarity, and religiosity, through embodied learning and collective experience. The study further identifies that the sustainability of these values is challenged by modernization, generational shifts, and the decline of traditional transmission mechanisms. Strategic efforts such as educational integration, community revitalization, and digital adaptation emerge as critical pathways for sustaining their relevance. This research contributes to the discourse on culture-based character education by offering a contextualized framework that bridges traditional knowledge systems with contemporary pedagogical approaches.